Work Engagement and Work Experience as Determinants of Bus Driver Performance at PO Menggala Garuda Lokatara on the Surabaya–Malang Route - Ardiyansyah, Rangga; Rini, Hesty Prima (PT Larva Wijaya Penerbit, 2025)
The objective of this study is to assess how work engagement and past work experience affect the performance of bus drivers at PO Menggala Garuda Lokatara on the Surabaya–Malang route. The research applied a quantitative design with a total of 44 bus drivers as respondents, all of whom operate along the Surabaya–Malang line. The responses collected via questionnaires were analysed using the PLS-SEM approach with the aid of SmartPLS software. A total sampling method was applied, encompassing all 44 participants in the study. It was found that driver performance is positively affected by work engagement as well as by work experience, with both effects being significant. These outcomes emphasize the critical role of employee engagement and accumulated experience in enhancing both the efficiency and overall performance of bus drivers.